Public-private partnership as a mechanism for attracting human resources in the reconstruction of sports infrastructure in post-war Ukraine - Stativka , Natalia; Bodnar , Kateryna (Pressing Problems of Public Administration, 2024)
This article explores the problem of staffing the restoration of war-damaged sports facilities through the use of public-private partnership (PPP) models. The authors note the exacerbation of the pre-war shortage of qualified personnel in the industry and the growing demands of digital transformation, which actualize the search for innovative forms of interaction between the state, business and education. A literature review revealed the fragmented nature of research on the personnel aspects of PPPs, especially in the context of post-war reconstruction. At the same time, the US experience in strategically attracting foreign specialists for the development of critical industries is interesting. The research results reveal the key factors of the effectiveness of public-private partnerships for attracting human resources in the process of rebuilding sports infrastructure in the conditions of post-war transformation. Attention is paid to the use of digital technologies to optimize cooperation between public and private project participants. Based on leading global practices, the authors propose a conceptual model of «Strategic Partnership for Sustainable Recovery». It provides for selective projects, involvement of experienced international operators, integration of sustainable development and inclusion goals into contracts, flexible risk-sharing mechanisms, and targeted employment programs for vulnerable groups. Basic scenarios for the development of PPPs are substantiated, with a focus on the formation of internal human resources through training, professional development and dual education. The creation of industry personnel consortia is proposed to coordinate diverse initiatives. The article contains valuable theoretical generalizations and practical recommendations on unlocking the human resource potential of PPPs as a driver of the innovative revival of Ukraine’s sports infrastructure in the post-war period.